Asymmetrical Flow Field-Flow Fractionation Methods for Quantitative Determination and Size Characterization of Thiols and for Mercury Size Speciation Analysis in Organic Matter-Rich Natural Waters - Worms, Isabelle A. M.; Kavanagh, Killian; Moulin, Elodie; Regier, Nicole; Slaveykova, Vera I. (Frontiers in Chemistry, 2022)
Asymmetrical flow field-flow fractionation (AF4) efficiently separates various macromolecules and nano-components of natural waters according to their hydrodynamic sizes. The online coupling of AF4 with fluorescence (Fluo) and UV absorbance (UV) detectors (FluoD and UVD, respectively) and inductively coupled plasma–mass spectrometry (ICP-MS) provides multidimensional information. This makes it a powerful tool to characterize and quantify the size distributions of organic and inorganic nano-sized components and their interaction with trace metals. In this study, we developed a method combining thiol labeling by monobromo(trimethylammonio)bimane bromide (qBBr) with AF4–FluoD to determine the size distribution and the quantities of thiols in the macromolecular dissolved organic matter (DOM) present in highly colored DOM-rich water sampled from Shuya River and Lake Onego, Russia. We found that the qBBr-labeled components of DOM (qB-DOM) were of humic type, characterized by a low hydrodynamic size (dh < 2 nm), and have concentrations <0.3 μM. After enrichment with mercury, the complexes formed between the nano-sized components and Hg were analyzed using AF4–ICP-MS. The elution profile of Hg followed the distribution of the UV-absorbing components of DOM, characterized by slightly higher sizes than qB-DOM. Only a small proportion of Hg was associated with the larger-sized components containing Fe and Mn, probably inorganic oxides that were identified in most of the samples from river to lake. The size distribution of the Hg–DOM complexes was enlarged when the concentration of added Hg increased (from 10 to 100 nM). This was explained by the presence of small iron oxides, overlapping the size distribution of Hg–DOM, on which Hg bound to a small proportion. In addition, to provide information on the dispersion of macromolecular thiols in colored DOM-rich natural water, our study also illustrated the potential of AF4–FluoD–UVD–ICP-MS to trace or quantify dynamic changes while Hg binds to the natural nano-colloidal components of surface water.